2019
DOI: 10.1136/bmjopen-2019-030708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and types of sexual inactivity in Britain: analyses of national cross-sectional probability survey data

Abstract: ObjectivesTo examine how prevalence and context of sexual inactivity varies across the life-course, assess dissatisfaction with sex life among those who are sexually inactive and identify associations with factors that may represent reasons for sexual inactivity.DesignAnalysis of cross-sectional probability sample survey data.SettingBritish general population.Participants14 623 participants (n men: 6045 unweighted, 7245 weighted), aged 16–74 years, of the third National Survey of Sexual Attitudes and Lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…Because our sample was limited to individuals ages 14–49, we were unable to examine sexual behavior trends among people aged 50 and older. However, our findings align with studies that have found greater proportions of young people reporting no partnered sexual behaviors in the prior year (e.g., Burghardt et al, 2020 ; Ghaznavi et al, 2019 ; Ueda & Mercer, 2019 ; Ueda et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Because our sample was limited to individuals ages 14–49, we were unable to examine sexual behavior trends among people aged 50 and older. However, our findings align with studies that have found greater proportions of young people reporting no partnered sexual behaviors in the prior year (e.g., Burghardt et al, 2020 ; Ghaznavi et al, 2019 ; Ueda & Mercer, 2019 ; Ueda et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of sexual inactivity in this study is higher than in other populations. The prevalence of male sexual inactivity in the general population in the US and Britain are 15.2% and 15.9%, respectively [10,20]. The prevalence reported in patients receiving opioid replacement treatment by Lugoboni et al [18] was comparable to the general population, but was four times lower than found in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…Disturbance of sexual function can affect quality of life [7,8] and relationships [9]. In the male general population, sexual inactivity ranges between 15.9% to 17.6% [10,11]. The prevalence of sexual inactivity is higher in people with comorbidities such as diabetes, hypertension, psychiatry conditions, and human immunodeficiency virus (HIV), than the general population [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…showing associations between lower income and measures of sexual inactivity [12][13][14]29 and decreased appeal in the mating market for men. [30][31][32][33] Given the widening disparities in economic security (some of which are more pronounced among young men), 34 the preference for men of higher socioeconomic status, and the larger number of college-educated young women than men in the US, it has been suggested that a subset of young men find it difficult to establish themselves in the heterosexual mating market.…”
Section: Jama Network Open | Public Healthmentioning
confidence: 99%